Characteristics and Incidence of Inpatient Ophthalmology Consultations to Screen for Papilledema - Belin, Peter J.; Greaves, Giovanni H.; Winokur, Jules; Gorski, Matthew (Journal of Academic Ophthalmology, 2019)
Objective A frequent reason for ophthalmology consultation is to rule out papilledema. The purpose of this study is to evaluate the incidence of consultations to screen for papilledema in an acute inpatient setting and determine the frequency and factors associated with a positive diagnosis of bilateral optic nerve swelling.Methods A retrospective chart review was performed of consecutive adult and pediatric inpatient ophthalmology consultations at a tertiary hospital system to “rule out papilledema” from September through November 2016. All patients had a detailed neuro-ophthalmology examination including a dilated fundus exam.Results A total of 36 consults—13 males and 23 females—with a mean age of 19.8 (range: 3–71) years were called to screen for papilledema. The most common service to request the consult was pediatrics (44%), followed by neurosurgery (42%), medicine (8%), and neurology (6%). The most frequent reason for consultation was headache (61%), followed by visual changes (30.5%) and nausea/vomiting (25%). A positive diagnosis of bilateral optic nerve swelling occurred in 14% (5/36) of consults. Of these five consults, four of them were sent into the hospital by an ophthalmologist who noted the bilateral optic nerve swelling and one was noted by an emergency room pediatrician.Conclusion No new cases of bilateral optic nerve swelling were found in screening consults to “rule out papilledema.” All of the positive diagnoses in our study had been previously identified by another physician and known to the primary team prior to ophthalmology consultation. Screening consultations for optic nerve swelling may not be an effective way to rule out papilledema.
Keywords: papilledema; optic nerve edema; ophthalmology consultations; screening